Mercury contents in commercial Billfish species of the Western Central Atlantic: Assessing the potential risks to human health of Billfish consumption. (April 2020) - Bille, Laura; Crovato, Stefania; Manfrin, Amedeo; Dalla Pozza, Manuela; Toson, Marica; Franzago, Eleonora; Pinto, Anna; Mascarello, Giulia; Muzzolon, Orietta; Tosi, Federica; Negroni, Gianluigi; Cappi, Gualberto; et al.
Abstract: Purpose of the present study was to evaluate the total Hg (THg) level in Billfish caught in the Western Central Atlantic and to assess the potential health consequences due to consumption for people living in Grenada (GR) and in the Dominican Republic (DR). Consumption data were collected through the administration of an online questionnaire and THg was measured in samples of Atlantic sailfish ( Istiophorus platypterus, n = 38), Blue Marlin ( Makaira nigricans, n = 62) and White marlin ( Kajikia albida, n = 45) collected at the main fish landing point in GR and in DR. The potential health risk for different consumer groups was evaluated by calculating the estimated metal weekly intake rate (MWIR; μg kg −1 body weight), that was compared to the provisional tolerable weekly intake (PTWI) for methylmercury (MeHg), and the total hazard quotient (THQ). A conservative approach was applied considering that THg was detected in its more toxic form, i.e. MeHg. The following levels of THg values were detected: Blue Marlin (0.09–6.23 mg kg −1 ), White Marlin (0.05–3.21 mg kg −1 ) and Atlantic sailfish (0.03–0.64 mg kg −1 ). For average consumers, the estimated MWIR minimally contributed to the PTWI and the THQ values turned out to be far below 1 in both the studied countries. Differently, the results regarding high consumers (95 percentile) raised some concerns. Highlights: Total Hg was tested in three billfish species in Grenada and the Dominican Republic. Higher Total Hg levels were detected in Blue Marlin (range: 0.09–6.23 mg kg −1 ). An online questionnaire was used to collect data regarding billfish consumption by local people. For average consumers, experiencing adverse effects emerged to be unlikely. The results regarding high consumers raised some concerns.